Mri Evaluation of Metal Acupuncture Needles. Issue 4 (December 2013) - Mei, Ling; Long, Xiaojing; Diao, Yanjun; Yu, Haibo; Yang, Wanzhang; Standish, Leanna J; Qiu, Bensheng
Objective: To evaluate the MR compatibility of three metal acupuncture needles (a standard stainless steel needle, a gold needle and an austenitic stainless steel needle) by comparing their imaging artefacts, radiofrequency heating effects and ease of operation. Methods: The MRI artefacts of the three metal needles were first evaluated by placing them in an agar gel phantom and performing MRI of the phantom. The increase in temperature during MRI was recorded using an MR-compatible fibreoptic thermometer. MRI of acupuncture at SP6 was performed using the MR-compatible gold needle and the austenitic stainless steel needle. Results: The standard stainless steel acupuncture needle produced large imaging artefacts on MRI. The gold needle was superior for MRI but not rigid enough for some clinical applications such as scalp acupuncture. The austenitic stainless steel needle is non-ferromagnetic and compatible with MRI. None of these acupuncture needles introduced radiofrequency heating during MRI. Conclusions: The evaluation of MR compatibility showed that gold and austenitic stainless steel needles are MR-compatible and therefore can be used for MRI of acupuncture.